A Hybrid Approach to Raising Digital Literacy among Adolescents in KSA Using a Mobile Application - Benaida, Mohamed; bin Youssef Shaheen, Abdul Rahman; Alam, Tanweer; bin Saad Khalifa, Abdul Hakam (International Journal of Interactive Mobile Technologies (iJIM), 2025)
As digital technologies and the Internet evolve, digital issues are becoming more prevalent and are a serious concern due to their increased level of integration in our daily lives. Many users lack the necessary digital literacy to protect themselves and their communities from such issues. Background research reveals that adolescents in Saudi Arabia are particularly vulnerable to these issues, also supported by the studies pre-test for students (15.8%). This highlights a gap regarding preventative measures that researchers aim to fill. This study investigates the effectiveness of integrating a dedicated mobile application focused on raising awareness regarding digital issues such as cyberbullying within a hybrid teaching framework amongst primary and middle school students in Saudi Arabia. The application’s features, including but not limited to pre-tests, post-tests, lecture material, and progress monitoring, along with its ease of use, are designed to efficiently achieve digital issue learning outcomes. To assess this hybrid approach toward raising awareness of digital issues, this study gathers 30 participants and splits them into three groups: group one (hybrid), group two (traditional), and group three (online only). The results, which were analysed via one-way analysis of variance (ANOVA) and Tukey’s honest significant difference (HSD) post-hoc test, demonstrate a significant advantage in the increased level of awareness of students from the first group. This indicates that our mobile application in hybrid settings is significantly more effective in enhancing knowledge retention amongst students and raising their level of awareness of digital issues.